Meningkatkan Kemampuan Berpikir Kritis dalam Penerapan PjBL pada Dinamika Fluida: Studi Literatur - Nurul Wahdah; Kuncoro Asih Nugroho; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to comprehend and describe the application of project-based learning integrated STEM (science, technology, engineering, and mathematics), or PjBL-STEM, to the study of fluid dynamics in order to improve critical thinking skills. Utilizing qualitative data collection methods, such as literature studies, is the research methodology used in this project. Theoretical sources that are relevant to the issues identified are searched for to collect data for this study. The data obtained is subsequently examined using descriptive analysis techniques. According to the data analysis, the N-gain score revealed an improvement in students' critical thinking skills. These conclusions are also supported by other pertinent investigations. According to a review of the research, using PjBL-STEM to study fluid dynamics may enhance critical thinking skills.